Analysis of the Suitability of the Head Nurse's Leadership Style Mediated by Job Satisfaction and Organizational Commitment to Nurse Performance at Pidie Jaya Regional General Hospital - Dian Melani; Ermi Girsang; Tan Suyono (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2025)
This study examines the relationship between the leadership styles of nurse managers, job satisfaction, organizational commitment, and their combined influence on nurse performance in Pidie Jaya Regional General Hospital. Using a qualitative approach, the research explores how transformational and transactional leadership styles affect organizational outcomes through the mediating variables of job satisfaction and commitment. The findings contribute to understanding the dynamics of effective nursing leadership in improving healthcare delivery.